2015
DOI: 10.4049/jimmunol.1401415
|View full text |Cite
|
Sign up to set email alerts
|

DAP12 Expression in Lung Macrophages Mediates Ischemia/Reperfusion Injury by Promoting Neutrophil Extravasation

Abstract: Neutrophils are critical mediators of innate immune responses and contribute to tissue injury. However, immune pathways that regulate neutrophil recruitment to injured tissues during noninfectious inflammation remain poorly understood. DAP12 is a cell-membrane associated protein that is expressed in myeloid cells and can either augment or dampen innate inflammatory responses during infections. To elucidate the role of DAP12 in pulmonary ischemia-reperfusion injury, we took advantage of a clinically relevant mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 47 publications
0
57
1
Order By: Relevance
“…For example, work from our group and others has demonstrated that alveolar macrophages contribute to pulmonary injury in the setting of sterile inflammation (16, 17). Alternatively, microglia plays a protective role after brain injury by modulating synapses (18).…”
Section: Discussionmentioning
confidence: 99%
“…For example, work from our group and others has demonstrated that alveolar macrophages contribute to pulmonary injury in the setting of sterile inflammation (16, 17). Alternatively, microglia plays a protective role after brain injury by modulating synapses (18).…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of our understanding of this relationship has come from experimental lung injury models showing that the initial recruitment of neutrophils was triggered by DAMP release. 3437 As suggested by the “Danger Hypothesis” noted earlier, DAMPs stimulated cognate PRRs to induce the expression of ELR + CXC chemokines and IL-1β, both of which were found to promote expression of adhesion molecules on the luminal surface of vascular endothelium to stimulate neutrophil transendothelial migration into interstitial tissues. 38 In particular, early expression of IL-17, 39 a well-established stimulator of ELR + CXC chemokines, 40 may play a critical role in early neutrophil graft sequestration.…”
Section: Neutrophilsmentioning
confidence: 91%
“…Both IRI and PGD are characterized by early neutrophil infiltration of the alveolar spaces and recent studies have shown that this leads to the formation of neutrophil extracellular traps (NETs) and lung injury (33). Indeed, macrophage-induced early reperfusion injury and neutrophil recruitment has been postulated and verified by several groups using animal models of both warm and cold ischemia (5357), but there is some conflicting evidence as to whether depletion of alveolar macrophages is protective or injurious (58). …”
Section: Ischemia-reperfusion Injury and Primary Graft Dysfunctionmentioning
confidence: 99%